Impact of International Remittances on Schooling in the Philippines: Does the Relationship to the Household Head Matter? - Tomoki FUJII (Institutional Knowledge at Singapore Management University, 2015)
We study the impact of international remittances on schooling in the Philippines, taking into account the school-age individual's relationship to the household head. This consideration is important because employment opportunities abroad may be taken at the expense of the quality of child rearing. Our estimation results indicate that there are, indeed, significant negative guardian effects on school attendance and education expenditures when children with overseas parents are looked after by a relative other than a parent or grandparent. However, these negative effects tend to be outweighed by the positive impact of remittance flows from overseas.